2022
DOI: 10.21203/rs.3.rs-1394191/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Radiative Cooling Sorbent towards High Performance All Weather Ambient Water Harvesting

Abstract: Emerging atmospheric water harvesting (AWH) technologies promise water supply to underdeveloped regions that have no access to liquid water resources. The prevailing AWH systems, including condensation- or sorption-based, mostly rely on a single mechanism and thus have a limited range of working conditions and inferior performance. In this study, we synergistically integrate multiple mechanisms, including thermosorption effect, radiative cooling, and multiscale cellulose-water interactions, and demonstrate a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…[49] Grasping energy from nature, some recent progress utilized radiative cooling (RC) to provide a cooling source to fabricate a passive CSAWH. [32,50] To this end, the extra cooling energy for adsorption is free from the sky and the cooling capacity could even achieve 145 W m −2 because the arid climate (low humidity) is beneficial to improving cooling capacity. Although the effect of radiative cooling can give a sub-ambient temperature with a limit temperature difference of ≈8 °C, [51] there is nearly no cooling capacity at this temperature difference.…”
Section: Broaden the Sorbents Suitabilitymentioning
confidence: 99%
“…[49] Grasping energy from nature, some recent progress utilized radiative cooling (RC) to provide a cooling source to fabricate a passive CSAWH. [32,50] To this end, the extra cooling energy for adsorption is free from the sky and the cooling capacity could even achieve 145 W m −2 because the arid climate (low humidity) is beneficial to improving cooling capacity. Although the effect of radiative cooling can give a sub-ambient temperature with a limit temperature difference of ≈8 °C, [51] there is nearly no cooling capacity at this temperature difference.…”
Section: Broaden the Sorbents Suitabilitymentioning
confidence: 99%
“…Kim et al first reported the potential of nighttime radiative cooling to lower the temperature of sorbents, allowing the sorbents with mild water affinity to work under low RH conditions. 9 Recently, Wang et al 36 and Zhu et al 37 developed multifunctional sorbents with extraordinary water harvesting capacity, high stability, and radiative cooling functions. The nighttime radiative cooling enabled a low sorption temperature to facilitate the exothermic water harvesting process.…”
Section: Introductionmentioning
confidence: 99%